Determinants of Equilibrium Selection in Network Formation - An Experiment - Hoyer, Britta; Rosenkranz, Stephanie (Games)

A Survey of Recent Trends in Multiobjective Optimal Control—Surrogate Models, Feedback Control and Objective Reduction - Peitz, Sebastian; Dellnitz, Michael (Mathematical and Computational Applications)
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. The advances in algorithms and the increasing interest in Pareto-optimal solutions have led to a wide range of new applications related to optimal and feedback control, which results in new challenges such as expensive models or real-time applicability. Since the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging, which is particularly problematic when the objectives are costly to evaluate or when a solution has to be presented very quickly. This article gives an overview of recent developments in accelerating multiobjective optimal control for complex problems where either PDE constraints are present or where a feedback behavior has to be achieved. In the first case, surrogate models yield significant speed-ups. Besides classical meta-modeling techniques for multiobjective optimization, a promising alternative for control problems is to introduce a surrogate model for the system dynamics. In the case of real-time requirements, various promising model predictive control approaches have been proposed, using either fast online solvers or offline-online decomposition. We also briefly comment on dimension reduction in many-objective optimization problems as another technique for reducing the numerical effort.

Unveiling and Imaging Degenerate States in Plasmonic Nanoparticles with Nanometer Resolution - Myroshnychenko, Viktor; Nishio, Natsuki; García de Abajo, F. Javier; Förstner, Jens; Yamamoto, Naoki (ACS Nano)
Metal nanoparticles host localized plasmon excitations that allow the manipulation of optical fields at the nanoscale. Despite the availability of several techniques for imaging plasmons, direct access into the symmetries of these excitations remains elusive, thus hindering progress in the development of applications. Here, we present a combination of angle-, polarization-, and space-resolved cathodoluminescence spectroscopy methods to selectively access the symmetry and degeneracy of plasmonic states in lithographically fabricated gold nanoprisms. We experimentally reveal and spatially map degenerate states of multipole plasmon modes with nanometer spatial resolution and further provide recipes for resolving optically dark and out-of-plane modes. Full-wave simulations in conjunction with a simple tight-binding model explain the complex plasmon structure in these particles and reveal intriguing mode-symmetry phenomena. Our approach introduces systematics for a comprehensive symmetry characterization of plasmonic states in high-symmetry nanostructures.
Keywords: tet_topic_plasmonics

Intensity surge and negative polarization of light from compact irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We study the dependence of the intensity and linear polarization of light scattered by isolated particles with the compact irregular shape on their size using the discontinuous Galerkin time domain numerical method. The size parameter of particles varies in the range of X = 10 to 150, and the complex refractive index is m = 1.5 + 0i. Our results show that the backscattering negative polarization branch weakens monotonously, but does not disappear at large sizes, up to the geometrical optics regime, and can be simulated without accounting for wave effects. The intensity backscattering surge becomes narrower with increasing particle size. For X = 150, the surge width is several degrees.
Keywords: tet_topic_scattering

Towards a Multi-Stage Approach to Detect Privacy Breaches in Physician Reviews - Bäumer, Frederik Simon; Kersting, Joschka; Orlikowski, Matthias; Geierhos, Michaela (Proceedings of the Posters and Demos Track of the 14th International Conference on Semantic Systems co-located with the 14th International Conference on Semantic Systems (SEMANTiCS 2018))
Physician Review Websites allow users to evaluate their experiences with health services. As these evaluations are regularly contextualized with facts from users’ private lives, they often accidentally disclose personal information on the Web. This poses a serious threat to users’ privacy. In this paper, we report on early work in progress on “Text Broom”, a tool to detect privacy breaches in user-generated texts. For this purpose, we conceptualize a pipeline which combines methods of Natural Language Processing such as Named Entity Recognition, linguistic patterns and domain-specific Machine Learning approaches which have the potential to recognize privacy violations with wide coverage. A prototypical web application is openly accesible.
Keywords: Detection of Privacy Violations; Physician Reviews

Flexible Ambiguity Resolution and Incompleteness Detection in Requirements Descriptions via an Indicator-based Configuration of Text Analysis Pipelines - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 51st Hawaii International Conference on System Sciences)
Natural language software requirements descriptions enable end users to formulate their wishes and expectations for a future software product without much prior knowledge in requirements engineering. However, these descriptions are susceptible to linguistic inaccuracies such as ambiguities and incompleteness that can harm the development process. There is a number of software solutions that can detect deficits in requirements descriptions and partially solve them, but they are often hard to use and not suitable for end users. For this reason, we develop a software system that helps end-users to create unambiguous and complete requirements descriptions by combining existing expert tools and controlling them using automatic compensation strategies. In order to recognize the necessity of individual compensation methods in the descriptions, we have developed linguistic indicators, which we present in this paper. Based on these indicators, the whole text analysis pipeline is ad-hoc configured and thus adapted to the individual circumstances of a requirements description.
Keywords: Software Product Lines: Engineering; Services; and Management; Ambiguities; Incompleteness; Natural Language Processing; Software Requirements

Tax Avoidance and Accounting Conservatism - Bornemann, Tobias
This study analyzes the relation between accounting conservatism, future tax rate cuts and countries’ level of book-tax conformity. Firms have an incentive to increase conservatism in ﬁnancial reporting when a tax rate cut is imminent to shift taxable income into the lower taxed future. Using a panel of ﬁrms across 18 countries from 1995 to 2010 I ﬁnd that conditional conservatism is positively and signiﬁcantly associated with future tax rate cuts when book-tax conformity is high. This eﬀect is particularly pronounced for ﬁrms that concentrate the majority of their operations in the country in which the tax rate is cut. In contrast, there is no signiﬁcant relation between future tax rate cuts and unconditional conservatism.

Taxation and Agency Conflicts between Firm Owners and Managers: A Review - Bauer, Thomas; Kourouxous, Thomas; Krenn, Peter (Business Research)
When analyzing the influence of taxation on agency conflicts between firm owners and managers, one can draw on theoretical principal–agent literature from various research fields. In recent years, this interdisciplinary research has grown significantly covering research with regards to optimal compensation, investment decisions, tax avoidance and transfer pricing while analyzing the effects of corporate income taxes, wage taxes, bonus taxes and shareholder taxes. Our paper provides a comprehensive review of analytical literature that studies the influence of taxation on agency conflicts between firm owners and managers. Above and beyond summarizing research findings, we discuss how taxes are commonly implemented in agency models, derive empirical predictions, and identify research gaps for future tax research.

The more the merrier? Immigrant share and entrepreneurial activities. - Li, C; Dau, L A; Kabst, Rüdiger (Entrepreneurship Theory and Practice.)

Embracing the foreign: Cultural attractiveness and international strategy. - Li, C; Brodbeck, F C; Shenkar, O; Ponzi, L J; Fischer, J (Strategic Management Journal.)